4-Chlorophenyl quinoline-2-carboxylate - Fazal, E. (International Union of Crystallography, 2013)
In the title compound, C16H10ClNO2, the dihedral angle between the quinoline ring system and the benzene ring is 14.7 (5)°. The carboxylate group is twisted from the mean planes of the quinoline ring system and the benzene ring by 17.7 (5) and 32.1 (4)°, respectively. In the crystal, inversion dimers are formed with the molecules linked by pairs of weak C—H⋯O interactions arising from an activated aromatic C atom adjacent to the C—Cl bond, generating R 2 2(14) loops.